Enhancing Avocado Farming Through Targeted Agricultural Extension for Knowledge Improvement in Composting and Cultivation Practices - Wiraguna, Edi; Rochmah, Hidayati Fatchur; Meliala, Merry Gloria; Azhar, Aidil; Dahliani, Lili; Purnamawati, Iis; Russianzi, Wanda; Muliasari, Ade Astri; Dardanella, Derry (Universitas Syiah Kuala, 2024)
This study evaluates the effectiveness of agricultural extension activities aimed at enhancing the knowledge of farmers of composting and good agricultural practices for avocados in Mulyaharja village, Bogor, West Java Province, conducted in October 2024. A total of 10 participants completed pre- and post-tests designed to measure their understanding of avocado cultivation and composting practices. Results showed a significant increase in knowledge regarding avocado cultivation, with scores rising from 64% to 79% post-intervention (P=0.049). However, the improvement in composting knowledge was minimal, increasing from 57% to 63%, which was not statistically significant (P=0.29). These findings indicate that targeted extension activities can effectively improve knowledge related to avocado farming while suggesting a need for more engaging methods to enhance composting knowledge. This research highlights the critical role of tailored extension services in promoting sustainable agricultural practices and enhancing the capabilities of farmers in the region.